2013
DOI: 10.1042/bj20120952
|View full text |Cite
|
Sign up to set email alerts
|

Rfa2 is specifically dephosphorylated by Pph3 in Candida albicans

Abstract: Rfa2 is a ssDNA (single-stranded DNA)-binding protein that plays an important role in DNA replication, recombination and repair. Rfa2 is regulated by phosphorylation, which alters its protein–protein interaction and protein–DNA interaction. In the present study, we found that the Pph3–Psy2 phosphatase complex is responsible for Rfa2 dephosphorylation both during normal G1-phase and under DNA replication stress in Candida albicans. Phosphorylated Rfa2 extracted from pph3Δ or psy2Δ G1 cells exhibited diminished … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…PP4 was also implicated in dephosphorylation of RPA2 in C. albicans and mammals (Lee et al, 2010; Wang et al, 2013), as well as mammalian 53BP1, KAP1, and CHD4 (Lee et al, 2012, 2014). Other mechanisms that downregulate the checkpoint act by degrading Mrc1 or human CLASPIN (Fong et al, 2013; Mailand et al, 2006; Peschiaroli et al, 2006), or by sequestering Rad9 by Rtt107-Slx4 in yeast (Ohouo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…PP4 was also implicated in dephosphorylation of RPA2 in C. albicans and mammals (Lee et al, 2010; Wang et al, 2013), as well as mammalian 53BP1, KAP1, and CHD4 (Lee et al, 2012, 2014). Other mechanisms that downregulate the checkpoint act by degrading Mrc1 or human CLASPIN (Fong et al, 2013; Mailand et al, 2006; Peschiaroli et al, 2006), or by sequestering Rad9 by Rtt107-Slx4 in yeast (Ohouo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…RPA2, which is a homolog of ScRfa2 in animal cells, undergoes phosphorylation upon DNA damage stress [26]. Previous studies in C. albicans demonstrated that Rad53 and Rfa2 are phosphorylated by Mec1, a homolog of ATM, in response to DNA damage [18,21,29]. Thus, the phosphorylation of Rad53 and Rfa2 is crucial for the DNA damage response.…”
Section: Discussionmentioning
confidence: 93%
“…5 and 6), suggesting that the role of Ppt1 in C. albicans is not conserved. Previously, we found that the protein phosphatases Glc7, Pph3 and Ptc2 are directly involved in cell cycle progression and the DNA damage response in C. albicans, implying that yeast cells mainly rely on these protein phosphatases in response to genotoxins [18,23,29]. Studies in S. cerevisiae have shown that Ppt1 specifically dephosphorylates Hsp90 via its TPR domain [16], and Hsp90 contributes to the DNA damage response to radiation in animal cells [31].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Dephosphorylation of C. albicans Rfa2 requires the Pph3–Psy2 phosphatase complex (Wang et al 2013; Gao et al 2014), and the PP2AC and PP4C phosphatases are necessary to dephosphorylate human RPA2 during the DNA-damage response (Feng et al 2009; Lee et al 2010). Mass spectrometry analysis of proteins isolated from unstressed C. albicans pph3 Δ mutant cells revealed five potential targets of phosphorylation in Rfa2, none of which were located within the first 40 amino acids.…”
mentioning
confidence: 99%